Legitimate Strategies for Countering Rumors: A Subjective Exploration of Quranic and Prophetic Guidance - Hakami, Ikram Hassan; Shehab, Ali bin Muhammad Ibrahim (Journal of Ecohumanism, 2025)
This study detects the Islamic strategies derived from the Quran and the Sunnah be employed to enhance intellectual awareness and confront digital rumors. It also analyzes the role of Saudi Arabia in combating rumors. The study used eclectic methods to achieve the research aim. It attains descriptive analytical to analyze concepts related to strategies, intellectual awareness, and digital rumors. It also followed the deductive approach to spots to strategies derive from the Quran and the Sunnah to confront digital rumors. It also used applied techniques to provide practical means and tools to enhance intellectual awareness and confront digital rumors, including the optimal use of digital tools to guide individuals and communities toward responsible media behavior. The study found that the Quran and Sunnah provide strategies to safeguard society from malicious rumors. It emphasizes the need to learn and teach these principles. The Islamic religion emphasizes adhering to the Muslim community and its leadership to maintain social cohesion. Therefore, causing harm through rumors is unjustified under any circumstances or pretexts. Furthermore, the analysis revealed that the Kingdom of Saudi Arabia has undertaken significant initiatives to immunize individuals against rumors. The study recommends addressing intellectual issues to be carried out by specialists in the Quran and Sunnah.